Promoting intercultural communicative competence, listening and speaking skills through videos in a colombian efl context (2023)
This research project focused on exploring the impact of Video-Based Instruction on students’ awareness regarding Intercultural Communicative Competence (ICC) and the improvement of the Listening and Speaking skills in tenth graders of a public and a special regimen school in an English as Foreign Language (EAL) setting. For this study, ICC refers to the ability that a person has to adapt in diverse scenarios without disregarding their own culture characteristics. It is based on knowledge, critical awareness, attitudes, interaction and relating skills. For this reason, it is our objective to use ICC as content to help students develop English Listening and Speaking skills through discussions about foreign and Colombian videos of celebrations with the purpose of increasing learners’ ICC based on tolerance, avoiding stereotypes and being empathetic to others. It is crucial to explore how to include ICC into the curriculum since English teaching in Colombia has focused on grammar instead of teaching language in context. The video-Based Instruction was the method implemented to carry out our bilingual lessons to enhance learners’ awareness regarding ICC. The data was gathered through semi-structured interviews, pre and post assessments, students’ journals and observations; we analyzed the outcome of our instruction to determine whether students gaised awareness of ICC and English Listening and Speaking skills. Findings of our research demonstrated that through the implementation of Video-Based Instruction method, and each ICC session, learners increased their ICC and their Listening and Speaking skills.